Series active power filter supplied by fuel cell for mitigating power quality issues - Abdallah Ben Abdelkader; Othmane Abdelkhalek; Youssef Mouloudi; Mohamed Amine Hartani; Benabid Slimane (Institute of Advanced Engineering and Science, 2020)
In this paper, the combination of the series active power filter (SAPF) with a fuel cell (FC) source is deliberated. The FC based on the SAPF aims to compensate voltage deviations or disturbances that occur in the system caused by power quality issues. The proposed system consists of a fuel cell source connected to the DC l ink through two DC-DC converters, the first extracts the maximum power of the FC source through pulse width modulation (PWM) signals generated from the maximum power point tracker (MPPT) controller. Thus, the second converter is used to regulate the high voltage side of the converter through closed control loops, in addition to a voltage source inverter (VSI) and a series injection transformer. Despite of fluctuations of the DC link during the compensation of the needed energy, MPPT and closed control loops generate PWM signals to the switching devices of DC-DC boost converters in order to extract maximum fuel cell power and to maintain the bus voltage within its limits and around its reference values respectively. The proposed topology is simulated in MATLAB/Simulink software, where simulation results show that the proposed FC based SAPF can efficiently reduce problems of voltage sags-wells and harmonics.